Leveraging Blockchain-based Smart Contracts to Develope Trustworthy Customer Agreements - Irawan, Bambang; Wahyu Sabiqudin, Muhammad; Anwar, Nizirwan; Tjahjono, Budi (Publisher Cv. Inara, 2023)
The With the advancement of computer, electronic, and telecommunications technology, there has been a significant change in the world of applications, which makes it easier for humans to carry out various activities, both at work and in interacting on social media.CV. Albahritech faces the challenge of not having a quick and easy office equipment maintenance application. This limitation can have a negative impact on company operations. Currently, the maintenance process still relies on communication via WhatsApp or phone, which causes customer appointments to be missed or forgotten due to the large number of calls for customer maintenance services that cannot be fulfilled. In addition, transactions and visit reports are not properly recorded, which can cause customers to experience delays in getting treatment services or even cause customers to look for other treatment services.The currently designed application uses a blockchain-like decentralized network model, known as a DApp. This DApp has several important features that utilize blockchain technology[1], including the ability to make payments using cryptocurrencies such as Ether and the feature to record service lists for customers. In this application, smart contracts are used to create a mechanism of trust and automation in agreements or deals between the parties involved. This ensures that agreements and transactions made within the app are transparent, secure, and without the need for a third party. In addition, the app also uses IPFS for customer data storage. IPFS is a peer-to-peer file distribution system that serves to store and distribute data on the interne[2]t. The use of IPFS in this application enables distributed and decentralized data storage, thereby improving data security and reliability. Keywords: Helpdesk, Ticketing, Blockchain, Smart Contract,IPFS.